KEANEKARAGAMAN JENIS LUMUT (BRYOPHYTA) BERDASARKAN KETINGGIAN DI GUNUNG RORE KAUTIMBU TAMAN NASIONAL LORE LINDU (TNLL) SULAWESI TENGAH - Agus Rahmatullah; Ramadhanil Ramadhanil; Mohammad Jamhari (Biocelebes, 2015)
Flora information of bryophyte in Sulawesi were limited found. Research on the bryophyte diversity at the different elevation of Mount Rore Kautimbu Lore Lindu National Park (LLNP) Central Sulawesi which had conducted from December 2013 to February 2014 was an effort to completed data and information of Bryophyte in Sulawesi. Bryophytes were sampled in three forest type s.a Sub-Montane Forest (1448 masl), Montane (2022 masl) and Alpine (2518 masl). In each zone was placed the plot size is 20 x 20 m sub-plots with measuring 1 x 1 m to substrate rocks, soil, decayed wood and plots 10 x 30 cm on the substrate of the tree. Data were analyzed by calculating the value of frequency, density, an important value index and the index of diversity according to the Shannon-Wiener. Research results gained as much as 41 species consists of 21 species mosses and 20 species of liverworts, which was dominated by the family dicranaceae. Based on the type of diversity Indices according to the Shannon-Wiener diversity was found in the highest zone of bryophytes and Alpine zones (H ' = 2.79) followed by Montane zone (H ' = 2,52) and Sub-Montane zone (H ' = 2.20).   Keywords:Bryophyta, Diversity, elevation, LLNP